Health education from the point of view of nurses of the family - Victor, Janaína Fonseca; Vieira, Neiva Francenely Cunha (Rev Rene, 2002)
This is a descriptive study with qualitative approach that aimed at knowing how the nurse of the Family Health Program sees health education as a working practice. For that, interview and observation of the participants were adopted. Outcomes showed that FHP nurses’ concepts fit the following categories: change of behavior, the person as the center and policy of personal strengthening. The work allowed to visualize the initial steps that have been adopted for the understanding of health education in a widened concept.